Issues of Qur’an Expression in Surat Al-Waqi’a (Badi 'Science) as a Model - uddin , Muhannad; Mjbel , Ahmed (Islamic Sciences Journal, 2023)
The research aims to uncover the secrets of the Qur’an expression as one of the most important pillars of rhetoric. The two researchers studied the Qur’an expression in Surat al-Waqi'ah. The research showed the importance of the Qur’an expression in the sciences of rhetoric, as alliteration, contradiction, mockery and turning is present within the folds of the blessed Qur’anic verses. In the surah, all of them indicate the greatness of the Qur’anic verses, and all of them are indications that the speech of Allah Almighty is miraculous in its terms, words and organization.In the first requirement under the title (The Virtues of the Surah, the arrangement of Surat al-Waqi’ah in the Qur’an, the number of its verses, words and letters, its virtues, Surat al-Waqi’ah is Meccan or Medinan . The suitability of the surah to what preceded it, the proportionality between the beginning and the end of the surah). As for the second requirement, it came under the title (moral enhancers, which are antithesis, verbal enhancers, gender, sarcasm, affirmation of praise in a manner similar to slander, the compatibility of the commas (assonance), turning around) We ask Allah to grant success He is able to do it .